2007
DOI: 10.1002/art.23153
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum nitrate and nitrite levels with longitudinal assessments of disease activity and damage in systemic lupus erythematosus and lupus nephritis

Abstract: Objective. Reactive intermediate production is an essential component of the innate immune response that is induced during disease activity in murine lupus. This study was undertaken to determine whether a marker of systemic nitric oxide (NO) production correlates with prospectively studied disease activity in human systemic lupus erythematosus (SLE) and lupus nephritis patients.Methods. Eighty-three SLE patients and 40 control subjects were studied longitudinally. The SLE group included 23 patients with lupus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Our laboratory and others demonstrated that inducible nitric oxide synthase expression was increased in PLN (3, 4) and that inducible nitric oxide synthase- and myeloperoxidase-mediated modifications of proteins (nitrotyrosine (NTyr)) were increased in the serum of lupus patients with LN, particularly among African-Americans (5). However, the importance of increased inducible nitric oxide synthase (iNOS)-mediated nitric oxide (NO) production in LN was questioned when genetic deletion of functional iNOS in lupus mouse models failed to reduce the onset of classic pathologic features of LN except vasculitis (6, 7).…”
Section: Introductionmentioning
confidence: 90%
“…Our laboratory and others demonstrated that inducible nitric oxide synthase expression was increased in PLN (3, 4) and that inducible nitric oxide synthase- and myeloperoxidase-mediated modifications of proteins (nitrotyrosine (NTyr)) were increased in the serum of lupus patients with LN, particularly among African-Americans (5). However, the importance of increased inducible nitric oxide synthase (iNOS)-mediated nitric oxide (NO) production in LN was questioned when genetic deletion of functional iNOS in lupus mouse models failed to reduce the onset of classic pathologic features of LN except vasculitis (6, 7).…”
Section: Introductionmentioning
confidence: 90%
“…32 All volunteers gave documented informed consent to participate in Institutional Review Board-approved protocols. Analyzed samples were from patients (predominantly African Americans) meeting American College of Rheumatology revised criteria for SLE 33 without nephritis, subjects with active LN at entry, 32 and control subjects without autoimmune or inflammatory disease. Spot urine and blood collections and clinical evaluations were performed at entry.…”
Section: Patient Renal Biopsies and Urine Samplesmentioning
confidence: 99%
“…Mesangial cells, such as macrophages, produce nitric oxide (NO), superoxide, and other inflammatory mediators in response to LPS, IFN-c and IL1b. [20][21][22] We and others [23][24][25][26] have reported iNOS expression in renal tissue of lupus patients and evidence of nitrated proteins in kidneys from MRL/lpr mice. In addition to NO, other inflammatory mediators released by mesangial cells have a pathogenic role in lupus (i.e.…”
Section: Mrl/mpj-fasmentioning
confidence: 99%